Effect of Acupressure of Xue Hai Point on Severity of Pain in Primary Dysmenorrhea - H. Ezadi (Ufuq-i Dānish, 2016)
Aims: There is a prevalence of dysmenorrhea in women. The treatment of the disease includes medication and non-medication treatments. The non-medication treatments, such as acupressure, are recently noticed by the patients. The aim of this study was to investigate the effects of pressure on the tenth spleen point on the pain severity in the primary dysmenorrhea.